Parâmetros genéticos, herança e seleção para múltiplas características no trigo - Pitana, Gabriel Pereira (2024)
Wheat cultivation faces a series of current and projected future challenges, especially in the face of climate change, environmental constraints, and economic and food security needs. The search for more productive cultivars with interesting traits is relentless in wheat genetic improvement programs worldwide. The objective of this study was to study and understand the genetic parameters, genetic inheritance, and simultaneous selection for multiple traits, with emphasis on ear germination in wheat populations. The cultivars Frontana, CD 1440, CD 105, and BRS Sabiá with levels of resistance to ear germination were selected as parents. These were crossed with each other, part of the F1 seeds were advanced to F2 generations and for the most divergent parents in spike germination (Frontana and BRS Sabiá) backcrosses were performed (RC1F1 and RC2F1). The F1, F2 generations and the parents of all populations were sown in the field in 2020. Each plot consisted of 4 lines of the F1 generation, 14 lines of the F2 generation and 4 lines of each of the parents for each combination. The F1 and F2 generations, together with the parents (Frontana and BRS Sabiá) and the backcrosses (RC1 and RC2), were sown in the field in 2021. Each plot consisted of 2 lines of the F1 generation, 14 lines of the F2 generation, 4 lines of backcrosses (RC1F1 and RC2F1) and 2 lines of each of the parents (Frontana and BRS Sabiá). The lines were 3 meters long, with a spacing of 34 cm between lines and 20 cm between plants, positioned in a homogeneous area. The experiment was set up in the second half of May 2021. For each individual plant, the characteristics of days from emergence to heading, plant height and number of tillers per plant were obtained. At the time of physiological maturity, the main spike of each plant was harvested for the germination test in the spike. The secondary spike of each plant of the parents, F1 and F2 generations were harvested and from these the characteristics, spike length, spike weight, number of spikelets per spike, grain weight per spike, number of grains per spike and germination in the spike were obtained. The remaining spikes of each plant were harvested and threshed separately, and the characteristic grain mass of the plant was obtained. The main tiller spikes were immersed in pots with 1 liter of water at room temperature for 8 hours and subjected to germination on germitest paper in a germination chamber. Seven days later, germination was read to a scale of 1 to 11. In addition to the averages, the phenotypic, genetic and environmental variance and the broad and narrow sense heritability were obtained, the latter only for the population with backcrosses. The gain by selection was also obtained, considering a selection rate of 20% and the number of genes. For all the studied traits, segregation in F2 tended towards one of the parents, in some cases as was the case for germination in the spike, segregating against the breeding objective. All traits presented quantitative inheritance, controlled by many genes and influenced by the environment. Simultaneous selection for multiple traits is complex, and the breeder should use associated methodologies. Germination in the spike has quantitative inheritance and segregation in F2 is strongly directed towards susceptible individuals.